(untitled) (Informatica, 2025)
The increasing complexity of cyber threats demands high-performance Network Intrusion Detection Systems (NIDS) that are both accurate and efficient. This study presents an optimized NIDS framework combining feature selection with ensemble learning. Experiments were performed on the CIC-IDS2017 dataset using a stratified train/test split of 70/30. Feature selection methods included Information Gain (24 features), Chi-square (χ2, 25 features), and Principal Component Analysis (PCA, 20 features). Bagging classifiers (Random Forest, Extra Trees, Bagged Decision Tree) and boosting classifiers (XGBoost, Gradient Boosting, LightGBM, AdaBoost, CatBoost) were evaluated. Using Information Gain selecting 24 features, Extra Trees achieved 99.98% accuracy with near-perfect precision, recall, and F1-score, and extremely low false positive and false negative rates of 0.0001397 and 0.0002597, respectively. Boosting-based models demonstrated superior sensitivity for minority attack classes, improving performance under imbalanced conditions. These results indicate that integrating feature selection with diverse ensemble techniques produces a scalable, interpretable, and highly effective NIDS suitable for practical cybersecurity applications.